Myofascial release effects in teachers' posture, muscle tension and voice quality: a randomized controlled trial - Cardoso, Ricardo (2023)
Summary: Objective. Myofascial release (MFR) comprises a set of manual therapeutic techniques applied to many conditions, but specific evidence concerning its effects on body posture, muscle tension and voice has been lacking. Thus, the aim of this study was to verify the effects of MFR in teachers’ posture, muscular tension and voice quality. Study Design. Randomized controlled trial − crossover. Methods. Twenty-four teachers, after completing a Sociodemographic and Clinical Questionnaire and providing written informed consent, were randomly distributed into two groups designated Group 1 (G1; n = 12; received MFR first) and Group 2 (G2; n = 12; belong to control group first). All participants received treatment and were into control group, since, after a 14 day period, procedures were switched between groups. Photogrammetry, muscle tension assessed through palpation, algometry, aerodynamic assessment of voice, acoustic and auditory-perceptual analysis of voice were performed before and after interventions. Results. Regarding voice, statistically significant differences were found when intervention was applied to both groups for maximum phonation time (MPT) (G1 P = 0.019; G2 P = 0.004). The acoustic variables did not differ. Concerning the auditory-perceptual analysis of voice statistically significant differences were found when intervention was applied in both groups for Grade in G2 (P = 0.046) and for Roughness in G1 (P = 0.025). Regarding the photogrammetry assessment statistically significant differences were found when intervention was applied to both groups in many parameters while as control group they did not. Concerning the algometry and muscle tension assessed through palpation statistically significant differences were found when intervention was applied in all muscles. Conclusions. Findings indicated that MFR seems to be an effective therapy in improving MPT, two subscales (Grade and Roughness) of the GRABASH scale, muscle tension assessed through palpation and algometry. Regarding photogrammetry, MFR had an immediately effect in improvement of the posture, especially related with head.